More Than a Harmful Practice: The Complexity of Gender Issues Within Child Marriage - Asriani, Desintha Dwi; Muharomah, Defirentia One; Mukhotib, Mukhotib MD; Parhas, Yan (Pusat Analisis Keparlemenan Badan Keahlian Sekretariat Jenderal DPR RI, 2025)
Child marriage remains persistent in Indonesia, rooted in entrenched gender norms and structural inequality. Although legal reforms have been introduced, their implementation remains limited due to gaps in knowledge production and dissemination between national and local actors. This study examines the complexity of child marriage using gender and intersectionality perspectives, focusing on socio-cultural, economic, and legal factors that contribute to its persistence in the Special Region of Yogyakarta following amendments to the 1974 Marriage Law. Using a phenomenological approach, data were collected through literature reviews, observations, and in-depth interviews with 40 participants, including youth, parents, community leaders, cadres, and policymakers in the Special Region of Yogyakarta. Findings reveal that traditional gender norms, limited reproductive health knowledge, economic pressures, and weak policy enforcement collectively reinforce child marriage practices. The study concludes by emphasizing the need for comprehensive sexuality education, integrated implementation of the Violence Law and Marriage Law, and stronger enforcement mechanisms to combat child marriage and promote gender equity. This article aims to provide policymakers and legislators, particularly Commissions VIII and X, with insight into the design and implementation of regulations, programs, and activities that promote gender justice and child protection.